Knowledge, attitudes and practices toward childhood vaccination among guardians in Chengdu, China: a cross-sectional study - Liu, Wen; Li, Hongxia; Qin, Ling; Wang, Hui; Zhu, Kai; Yang, Taoyi; Jia, Xufeng; Xu, Lanqian (Frontiers in Pediatrics, 2025)
BackgroundVaccination effectively prevents various infectious diseases and represents one of the most cost-effective health interventions. In China, childhood immunization programs have achieved remarkable success, but guardian knowledge, attitudes, and practices (KAP) regarding vaccination significantly influence immunization coverage. Understanding vaccination KAP among children's guardians in Chengdu is crucial for optimizing immunization programs.AimTo assess knowledge, attitudes, and practices regarding childhood vaccination among guardians in Chengdu's Third People's Hospital and identify associated factors to improve vaccination service quality.MethodsA cross-sectional survey was conducted among 612 guardians of children aged 0–6 years between January and June 2023. Participants were recruited through systematic sampling during vaccination visits, telephone appointments, and household surveys. A structured questionnaire assessed vaccination knowledge (13 items), attitudes (11 items), and practices (9 items). Data were analyzed using χ2 tests and logistic regression analysis (P < 0.05).ResultsAmong 612 participants (response rate 90.1%), 97.7% were aware that newborns require vaccination within 24 hours, but knowledge gaps existed regarding vaccine classifications (56.1% aware of Category I vaccines), adverse reactions (61.8%), and specific vaccines like meningococcal (47.1%) and hepatitis A (41.5%). Most guardians (85.1%) considered vaccination necessary, and 69.9% proactively sought vaccination services. However, only 23.4% were unaffected by negative media reports. Logistic regression revealed that higher education levels (OR = 1.51, 95%CI: 1.02–2.24), higher family income (OR = 1.80, 95%CI: 1.09–2.96), and better housing conditions (OR = 1.89, 95%CI: 1.03–3.45) were associated with better vaccination knowledge.ConclusionGuardians in Chengdu demonstrate positive attitudes toward vaccination but require improved knowledge, particularly regarding vaccine categories and safety. Targeted education programs should focus on vulnerable populations with lower education and income levels to enhance vaccination coverage and child health protection.